How Universities Work: Understanding Higher Education Organization in Northwest China - Berger, Joseph B.; Hudson, Katherine E.; Blanco Ramírez, Gerardo (Education Policy Analysis Archives, 2013)
This study explores models of educational management used in postsecondary institutions in the five northwestern provinces of the People’s Republic of China (Shaanxi, Xinjiang, Gansu, Qinghai, and Ningxia). As higher education in the People’s Republic of China expands and undergoes significant changes, a nuanced understanding of the organizational structures in Chinese higher education is increasingly important. This qualitative study included group interviews with university administrators from institutions in each of the five northwestern provinces. Drawing on Birnbaum’s (1988) seminal work describing models of organization in higher education in the United States, the findings suggest four models of organization that are for the Chinese context. These models are: Tiao-Kuai Xitong (Vertical-Horizontal system), Confucian Guanxi, Authoritarian, and Dialectical. The study explores the complexity and diversity that characterizes Chinese higher education with important implications for the ongoing educational reform within China, as well as for developing a more sophisticated contextualized notion of Chinese higher education in the West.